Design of a sewage sludge energy conversion technology introduction scenario for large city sewage treatment plants in Japan: Focusing on zero fuel consumption. (15th December 2022) - Wang, Kehua; Nakakubo, Toyohiko
Abstract: Current thermal treatment of dewatered sludge in Japan depends on incineration with no energy recovery, but new sewage sludge recycling strategies require that energy conversion technologies be applied to sewage treatment plants (STPs) in large cities. Strategic studies of decarbonization have shown that it is necessary to prioritize the reduction of CO2 emissions associated with the direct consumption of fossil fuels to work toward decarbonization. Therefore, a scenario that would minimize external fuel dependence was set in STPs located in 14 large cities in Japan. The scenario included a plan to introduce the following systems: incineration with waste heat power generation (WHPG) under no anaerobic digestion (AD), incineration with WHPG and a dryer under AD, and solid fuel conversion with AD. Results showed that the total energy balance in FY2030 would be reduced by 90% compared to that of FY2015. Digestion gas power generation in the scenario was reduced, and WHPG (2410 TJ) and solid fuel (1931 TJ) were recovered. Compared to FY2015, greenhouse gas (GHG) emissions in FY2030 were reduced by 118%, CO2 emissions from the use of A-heavy oil were eliminated, and N2 O emissions from incineration were reduced by 90%. In addition, analysis of the contribution of the scenario to GHG reduction in the boundary of national-scale sludge treatment in the sewerage sector showed that a 48% reduction was possible in FY2030 compared to FY2015, allowing Japan to fully achieve its medium-term emission reduction target (a 46% reduction) in this field. Highlights: We discussed five sewage sludge energy conversion technologies. We studied sewage treatment plants in 14 large cities in Japan. We designed a scenario for sludge treatment to minimize external fuel dependence. Greenhouse gas emissions and energy balance were used as evaluation indicators. Japan could meet its emission reduction target in sludge treatment field.